Holiness: a biblical, historical, and systematic theology - Ayars, Matthew I. (IVP Academic, an imprint of InterVarsity Press, 2023)
"In this volume, three scholars from the Wesleyan tradition offer a collective treatment of the theme of holiness that includes exegesis of key biblical passages, a survey across church history, and theological reflections on the relationship between entire sanctification and other doctrines. In addition, the co-authors constructively argue for a "Neo-Holiness" that encourages the pursuit of Christian perfection but avoids the pitfalls of Pelagianism by incorporating historic understandings of grace and the work of the Holy Spirit with the best of the Wesleyan tradition"--